2012
DOI: 10.3354/meps09654
|View full text |Cite
|
Sign up to set email alerts
|

Parasite communities indicate effects of cross-shelf distributions, but not mesoscale oceanographic features on northern California Current mid-trophic food web

Abstract: Mesoscale physical oceanographic features, such as jets and eddies, can influence the structure of marine ecosystems. We used trophically transmitted parasite communities of pelagic fishes in the northern California Current to examine effects of physical oceanographic features on pelagic ecosystem structure. We tested the hypotheses that (1) oceanographic features associated with a coastal promontory, Cape Blanco, Oregon (USA), produced a faunal break resulting in different pelagic ecosystems north and south o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…During this climate event, surface temperature (30.2°C) and salinity (35.5 ppt) in Acapulco Bay were significantly higher than in other sampling years (Table ). Abnormal increases in sea surface temperature can decrease the productivity of food webs, affecting the parasite transmission processes of many trophically transmitted parasites due to population decreases in potential intermediate or final hosts (Lamb et al, ; Jacobson et al, ; Oliva et al, ). In Acapulco Bay slight changes in the temperature and salinity parameters can be enough to generate notable changes in copepod community species composition throughout the year (Rojas‐Herrera, Violante‐Gonzalez, Garcia‐Ibañez, Villerias‐Salinas, & Moreno‐Diaz, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During this climate event, surface temperature (30.2°C) and salinity (35.5 ppt) in Acapulco Bay were significantly higher than in other sampling years (Table ). Abnormal increases in sea surface temperature can decrease the productivity of food webs, affecting the parasite transmission processes of many trophically transmitted parasites due to population decreases in potential intermediate or final hosts (Lamb et al, ; Jacobson et al, ; Oliva et al, ). In Acapulco Bay slight changes in the temperature and salinity parameters can be enough to generate notable changes in copepod community species composition throughout the year (Rojas‐Herrera, Violante‐Gonzalez, Garcia‐Ibañez, Villerias‐Salinas, & Moreno‐Diaz, ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most ubiquitous patterns in parasite ecology is high variability in parasite infection levels between populations of the same host species (Bagee, Poulin, & Valtonen, ; Marcogliese, ). Changes in local environmental factors, whether physical, oceanographic, or chemical, can facilitate the establishment and proliferation of certain parasites over time (Bagee et al, ; Jacobson et al, ; Lamb et al, ; Oliva et al, ). Therefore, local fluctuations in surface temperature and salinity, as well as changes in the diet of fish over time, may explain interannual variations in the infection levels of N. euthynni , C. caballeroi , H. ventricosa , Sicuotrema sp., Rhadinorhynchus sp., Anisakis sp., and Spinitectus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowhere is the idea that the same hosts in different food webs have different parasites more scrutinized than in fisheries management, an area where food web ecology and parasitology are most closely coupled. In this arena, it is well-established that accurate measures in fish migration patterns and stock assessment can be based on using parasites as biological tags [25-28]. Even fish stocks that are spatially or temporally separated by relatively short distances or times, can be identified by their parasites [29-31].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic identification of larval anisakids from a subset of Pacific sardine used in our study revealed a panmictic distribution of 3 populations of Anisakis spp., but these populations could not help inform stock structure or migration behavior of Pacific sardine in the CCS (Baldwin et al, 2011). The acanthocephalan Rhadinorhynchus trachuri, also longer-lived than the trematodes, is known to be a parasite of offshore fish species (George-Nascimento, 2000;Jacobson et al, 2012). Although less commonly recovered than the nematodes, it was recovered more often from the large Pacific sardine caught south of British Columbia.…”
Section: Parasites As Biological Tagsmentioning
confidence: 99%